(untitled) (Research, Society and Development, 2023)
Introduction: Physiological deterioration usually precedes serious patient events, such as death, cardiac arrest and admission to the intensive care unit. The additive early warning scores of physiological variables are an attempt to predict and prevent these events. Objective: To search for evidence in the literature on the applicability of the Alert NEWS and PEWS scores in cardiology for the preparation of practical recommendations. Method: Integrative literature review that included original articles from the MEDLINE, LILACS and BDENF databases, in the time frame from 2017 to 2022. The synthesis of the articles was done descriptively according to the type of approach. Results: 1147 articles were identified, of which seven were included in this review, published in English, Portuguese and Spanish. All articles sought to assess the applicability and confidence level of alert scores. Conclusion: The current alert system tools perform well in predicting death and cardiac arrest within a time frame of 24-48 hours, with a significant impact on hospital health outcomes and the reduction of cardiorespiratory cardiac arrest cases, Intensive Care Unit admission. Finally, early warning scores prove to be a reliable tool for detecting clinical conditions, the adoption of complementary factors such as biomarkers are an excellent complementary strategy in the detection of early deterioration in patients with acute heart failure.